THE EFFECTIVENESS OF EDMODO TOWARDS INDONESIAN EFL LEARNERS’ ENGLISH PROFICIENCY - Adawiyah, Rabiatun; Fithriani, Rahmah (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
As a result of the utilization of technological advances to achieve competency integration, the 4.0 technology era is gaining traction in the field of education. This study aims to explore the efficacy of using the Edmodo application as an online-based learning medium in order to improve the way in which EFL students learn English using technology. By  a mixed-methods research design, this study recruited twenty-two tenth graders in the Mathematics and Natural Science stream from an integrated Islamic senior high school in Aceh province, Indonesia. The data indicate that the majority of students possess the necessary devices to assist them in completing their tasks, and a significant proportion of them use these devices to play games and conduct research. By categorizing aspects and components, Edmodo improves students' vocabulary when used to assess their learning progress through assignments and quizzes. In addition, the students are more willing to request assistance from teachers and peers when using the application. Despite the fact that Edmodo requires a smartphone and a reliable internet connection to utilize it, the participants do not report having any significant issues with the two requirements, however, half of them report having trouble attaching assignments from different types of files such as Doc, Pdf, Video, and Audio. Overall, Edmodo is an outstanding and highly effective online resource for reading, writing, listening, and speaking English classes (e-learning).